Thematic resolution in conservation monitoring - assessment of the impact of classification detail on landscape analysis using the example of a biosphere reserve - Nienkemper, Pamela; Menz, Gunter (ERDKUNDE, 2016)
Monitoring landscape changes, especially conservation sites, is essential to sustain the environment and landscape diversity (Townsend et al. 2009). By now, it is evident that the thematic resolution of classified data sets affects the results of land use/land cover and landscapestructure analysis. However, uncertainty regarding the ambiguity of classification schemes and the impact of generalizations have not been sufficiently addressed until now (Lechner et al. 2012). This study applies digital vector data of biotope types and land use mapping to gain further systematic insights into these questions. The data sets are available area-wide for 2 years (1993 and 2006), using the example of the Rhoen biosphere reserve situated in central Germany. The objectives of the study are 1) to consider the effect of thematic resolution on the magnitude of land use and land cover changes, 2) to assess the impact of thematic resolution on the analysis of landscape patterns, and 3) to investigate which thematic resolution is most suitable to detect differences between the biosphere reserve zones regarding the temporal development of the landscape structure. To achieve the objectives, the initial data are reclassified into data sets, encompassing 9, 27, 59, and 204 classes. Results indicate a considerable effect on the magnitude of detectable landscape changes at low or very high thematic resolutions and a high sensitivity of landscape metrics. However, landscape metric values show not only quantitative (discrepancies of values) but also qualitative (divergences of direction of change) impacts.